The U.S. Influence on Eurasia and Research Opportunity - Megits, Nikolay (Journal of Eastern European and Central Asian Research (JEECAR), 2017)
Since the election of the new American President, Washington position has became even more uncertain toward U.S. political activities in Eurasia. NATO is slowly but surely moving toward the Russian border but in response, Russia, as reaction to the US and EU sanctions, becomes more and more aggressive toward its European neighbors. In today’s reality, President Putin is completely isolated by Western leaders and President Trump is cornered by the U.S. politicians and media. Current American and European domestic politics and their reflection on Eurasia provide enormous research opportunities in field of economics and international affairs.